2006
DOI: 10.3346/jkms.2006.21.5.843
|View full text |Cite
|
Sign up to set email alerts
|

The Stages of Change in Smoking Cessation in a Representative Sample of Korean Adult Smokers

Abstract: This study reports the stages of change in smoking cessation in a representative sample of Korean adult smokers. The study subjects, all adult smokers (n=2,422), were recruited from the second Korea National Health and Nutrition Examination Survey conducted in 2001. The stages of change were categorized using demographic (age and sex), socioeconomic (education, residence, and household income), and smoking characteristics (age at smoking onset, duration of smoking, and number of cigarettes smoked per day). Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…This finding is consistent with other studies in which the pre-contemplators have smoked more cigarettes per day than contemplators (DicClemente et al, 1991;Fava et al, 1995;Jhun and Seo, 2006). Additionally, a previous study in North America and Ethiopia showed that a high number of cigarette consumption among smokers was associated with lower motivation to quit smoking (Etter et al, 1997;Girma et al, 2011;Fu et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with other studies in which the pre-contemplators have smoked more cigarettes per day than contemplators (DicClemente et al, 1991;Fava et al, 1995;Jhun and Seo, 2006). Additionally, a previous study in North America and Ethiopia showed that a high number of cigarette consumption among smokers was associated with lower motivation to quit smoking (Etter et al, 1997;Girma et al, 2011;Fu et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, descriptions of smokers by stages of change continue to be widely used in clinical settings, because they are useful in directing the treatment, studying different populations of smokers, analysing profiles of subjects by stage over time (Connors et al, 2004), and assessing priorities for individuals or groups within a population that are targets of different health education strategies (Jhun and Seo, 2006;Wewers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…16 In the present study, age (1-year increase), income (lowest quartile), and occupational status (manual workers and unemployed individuals) were predictors of belonging to the group of smokers in the precontemplation stage (those with no intention to quit smoking). 9,11,17) Jhun and Seo 18) found that smokers with a longer smoking duration smokers who are unemployed and earning a low income. These results were also consistent with previous findings suggesting that manual workers have high rates of smoking and low rates of quitting.…”
Section: Discussionmentioning
confidence: 99%
“…12) Most studies have consistently reported similar results. 10,13,18) However, in one study conducted in China, income was not significantly related to smoking cessation. 19) The researchers attributed this finding to the rapid economic growth in China.…”
Section: Discussionmentioning
confidence: 99%